NALAR TEOLOGIS THAIFUR ALI WAFA AL-MADURI DALAM FIRDAUS AL-NA‘IM BI TAUDIHI MA‘ANI AYAT AL-QUR’AN AL-KARIM - Ahmad Qusyairi; Ahmad Zaidanil Kamil (Aqlam: Journal of Islam and Plurality, 2023)
This paper analyzes the interpretation of theological verses in tafsir Firdaws al-Na'im by Thaifur Ali Wafa al-Maduri. The author is a representation of Madurese religious authority because of his capacity as a pesantren cleric, mursyid tarekat, and structural NU figure in Sumenep. The research methods used in writing this article are library research and content analysis. By using critical discourse analysis, the results of this study show that the ideological tendency in Firdaws al-Na'im's interpretation can be seen from his interpretation of sensitive issues such as the theology of ru'yatullah, intercession, absolute will and justice of God. This tendency is due to the author's background as a local activist in Islamic boarding schools and traditional religious education that carries the ideology of Ahlussunnah wa al-Jama'ah. Thaifur Ali Wafa's scientific network that is connected to Middle Eastern scholars also strengthens this reason. This research is significant to portray how the intellectual relationship between Madurese Muslims and Middle Eastern Ulama has played an important role in bringing religious views and interpretations from the Middle East to the archipelago, including Madura.Keywords: Tafsir, Ideology, Thaifur Ali Wafa, Firdaws al-Na'imAbstrak: Tulisan ini menganalisis penafsiran ayat-ayat teologi dalam Firdaws al-Na‘im bi Tawdih Ma‘ani Ayat al-Qur’an al-Karim karya Thaifur Ali Wafa al-Maduri. Penulisnya adalah representasi dari otoritas keulamaan Madura karena kapasitasnya sebagai kiai pesantren, mursyid tarekat, dan tokoh NU Struktural di Sumenep. Metode penelitian yang digunakan dalam penulisan artikel ini adalah library research dan content analysis. Dengan menggunakan analisis wacana kritis, hasil penelitian ini menunjukkan bahwa kecenderungan ideologis dalam tafsir Firdaws al-Na’i>m dapat dilihat dari penafsirannya tentang isu-isu sensitif seperti teologi ru’yatullah, syafaat, kehendak mutlak dan keadilan Tuhan. Kecenderungannya terhadap Teologi Sunni ini disebabkan oleh latar kehidupan penulisnya sebagai aktifis lokal Islam pesantren dan pendidikan agama tradisional yang mengusung ideologi Ahlussunnah wa al-Jama’ah. Jaringan keilmuan Thaifur Ali Wafa yang terhubung dengan Ulama Timur Tengah juga memperkuat alasan tersebut. Penelitian ini signifikan untuk memotret bagaimana hubungan intelektual antara Muslim Madura dan Ulama Timur Tengah telah memainkan peran penting dalam membawa pandangan dan interpretasi keagamaan dari Timur Tengah ke wilayah Nusantara, termasuk Madura.Kata Kunci: Tafsir, Teologi, Thaifur ‘Ali Wafa, Firdaws al-Na‘im